The absorption of Lutensol, crystallinity and specific surface area depending on the zeolite crystallization temperature - Miladin Gligorić; Branko Škundrić; Časlav Lačnjevac (Zaštita Materijala)
In order to determine the dependence of absorption Lutensol, crystallinity and specific surface area of the zeolite synthesized at different temperatures crystallization was performed by a change in crystallinity (XRD), absorption Lutensol (LUT), average diameter of particles (DS50%), specific surface area and scanning electron microscopy (SEM) synthesized zeolites. Synthesis of the samples was held at a temperature of crystallization of 70, 75, 80, 85 and 90°C, while the raw material (Na-aluminate and of Na-silicate) were at temperatures of 90°C at the start of the synthesis. Average diameter of particles varied depending on the temperature of crystallization in accordance with the principles of autocatalytic nucleation and the 'memory effect' of the gel. Increasing the crystallinity of the synthesized samples with low oil absorption was observed in the analyzed system of the crystallization temperature of 75°C. At the temperature of crystallization 90°C crystallinity is significantly decrease at 37.87 % while absorption of Lutensol increases at the expense of increasing the of other types of non zeolites kinds. This is confirmed by SEM analiza. Specific surface area decreases with conclusive increase of the crystal phase zeolite A, from 11.30 to 2.14 m2/g zeolite.